A multidimensional approach for the identification of environmental and health wellness territories. (March 2020) - Perchinunno, Paola; Mongelli, Lucia; Rotondo, Francesco
Highlights: Multivariate statistical methods synthesize the relationships between the environmental indicators. Use of clustering makes it possible to identify continuous urban aggregation. Synthetic indicators help to compare different territories. Sustainability indicators are gaining lot of importance for urban policy making. Abstract: The evolution of the social and economic context in which the concept of wellbeing takes shape and the availability of new statistical information imposes constant checks on the set of indicators. The present work analyzes the relationships between environmental quality and health status indicators identified by the National Institute of Statistics (Istat) in Italian provinces. The data are analyzed through multivariate statistical methods (Totally Fuzzy and Relative) and methods of territorial classification (SaTScan) able to synthesize the various information and represent spatial distribution of environmental and health wellness.